Evaluating How Development Methodology Software is Used - Santiago Martinez; Maxx Johannes; Wei Xiang Tan (International Institute for Advanced Science & Technology (IIAST), 2024)
The success of software development projects heavily relies on effective project management software and the implementation of appropriate methodologies within the System Development Life Cycle (SDLC). Selecting and implementing suitable software design and development approaches pose significant challenges due to the inherent complexity of information system implementation. Tailored methodologies that cater to the diverse needs and standards of each organization are imperative. This research aims to address the multifaceted demands of software development by evaluating the practical usage of software development methodologies in industrial settings. Through evaluative research, valuable insights into the real-world application of these methodologies, their efficacy, and the challenges faced by practitioners are uncovered. By delving into usage patterns, encountered challenges, and potential avenues for improvement, this study seeks to contribute to the refinement of software development practices within industrial contexts. Ultimately, the goal is to foster greater efficiency, effectiveness, and innovation in software development methodologies, thereby enhancing the overall success of software projects.